Synthesis and antimicrobial activities of N6-hydroxyagelasine analogs and revision of the structure of ageloximes. Issue 4 (15th February 2019) - Paulsen, Britt; Fredriksen, Kim Alex; Petersen, Dirk; Maes, Louis; Matheeussen, An; Naemi, Ali-Oddin; Scheie, Anne Aamdal; Simm, Roger; Ma, Rui; Wan, Baojie; Franzblau, Scott; Gundersen, Lise-Lotte
Graphical abstract: Abstract: (+)- N 6 -Hydroxyagelasine D, the enantiomer of the proposed structure of (−)-ageloxime D, as well as N 6 -hydroxyagelasine analogs were synthesized by selective N-7 alkylation of N 6 - [ tert -butyl(dimethyl)silyloxy]-9-methyl-9 H -purin-6-amine in order to install the terpenoid side chain, followed by fluoride mediated removal of the TBDMS-protecting group. N 6 -Hydroxyagelasine D and the analog carrying a geranylgeranyl side chain displayed profound antimicrobial activities against several pathogenic bacteria and protozoa and inhibited bacterial biofilm formation. However these compounds were also toxic towards mammalian fibroblast cells (MRC-5). The spectral data of N 6 -hydroxyagelasine D did not match those reported for ageloxime D before. Hence, a revised structure of ageloxime D was proposed. Basic hydrolysis of agelasine D gave (+)- N -[4-amino-6-(methylamino)pyrimidin-5-yl]- N -copalylformamide, a compound with spectral data in full agreement with those reported for (−)-ageloxime D.